2014
DOI: 10.5946/ce.2014.47.4.295
|View full text |Cite
|
Sign up to set email alerts
|

Plastic and Biodegradable Stents for Complex and Refractory Benign Esophageal Strictures

Abstract: Endoscopic stent placement is a well-accepted and effective alternative treatment modality for complex and refractory esophageal strictures. Among the currently available types of stents, the partially covered self-expanding metal stent (SEMS) has a firm anchoring effect, preventing stent migration and ensuring effective covering of a narrowed segment. However, hyperplastic tissue reaction driven by the uncovered mesh may prevent easy and safe stent removal. As an alternative, a fully covered SEMS decreases th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 43 publications
1
46
0
4
Order By: Relevance
“…In terms of complications, the stent migration rates were variously 22.2 and 9.5 %, and post-stenting pain rates were 11.1 and 14.3 % [2,3]. These data showed results equal to or greater than those of SEPSs [9]. Van Boeckel and colleagues' report also showed that the success rate and complication rate of BD stents were equal to those of SEPSs, and that the rate of re-interventions after BD stenting was lower than that of SEPSs [12].…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…In terms of complications, the stent migration rates were variously 22.2 and 9.5 %, and post-stenting pain rates were 11.1 and 14.3 % [2,3]. These data showed results equal to or greater than those of SEPSs [9]. Van Boeckel and colleagues' report also showed that the success rate and complication rate of BD stents were equal to those of SEPSs, and that the rate of re-interventions after BD stenting was lower than that of SEPSs [12].…”
Section: Discussionsupporting
confidence: 45%
“…Currently, the use of SEPSs in patients with benign esophageal strictures has been proposed as an alternative to SEMS, because SEPSs have shown the same degree of relief of dysphagia; the lower major complication rate could reduce reactive tissue hyperplasia, and they could be removed more easily than SEMSs [7][8][9]. In pediatric patients, the use of SEMSs or SEPSs is limited, because the degree of damage to the esophageal wall following stenting is unclear [10,11], and esophageal stents have been fundamentally adapted only for the treatment of stenosis secondary to malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…[39] Newer modalities such as biodegradable stents and fully covered self-expandable metal stents are emerging alternatives for resistant strictures. [33,34,40]…”
Section: Esophageal Injuriesmentioning
confidence: 99%
“…However, most patients develop refractory esophageal strictures after extensive ESD. Although there are several treatments for refractory strictures, their utility is limited 3 4 5 6.…”
Section: Introductionmentioning
confidence: 99%